PENGGUNAAN PEREBAH SAPI SEBAGAI UPAYA PENINGKATAN KUALITAS KEGIATAN QURBAN - Nugroho, Arif Setyo; Fitra Wibawa; Joko Ismail (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
This community service activity aims to provide a solution for several mosques that do not have large areas of land when carrying out sacrificial services. Of course, some problems must be solved, such as how to carry out sacrificial activities by minimizing risks and not requiring large areas of land. The solution offered is when slaughtering sacrificial animals using a portable cow thrasher. The advantage of using a trestle is that laying down the cow when it is about to be slaughtered does not require many people, nor does it require a large area to lay the cow down. The area used for slaughtering is not so dirty because the blood can be poured into one place. Slaughtering was very fast, seven cows were slaughtered until the meat was separated, it only took approximately 3.45 hours. Cows do not get angry and go on a rampage, making it easier for the slaughter team to slaughter them.